Effect of aqueous polymer dispersions on properties of diclofenac/alginate beads and in vivo evaluation in rats - (:unkn) unknown (EDITIONS SANTE, 1997)
Alginates, which are natural biopolymers, were used to prepare controlled-release beads of diclofenac sodium in an entirely aqueous medium. Their morphology was evaluated by scanning electron microscopy. Calcium alginate beads with and without Aquacoat and Eudragit NE30D were tested for drug release rate in vitro and in vivo in Wistar rats for the inhibition of carrageenin-induced paw edema. Beads containing Eudragit NE30D provided a zero-order diclofenac sodium release rate. The beads released diclofenac sodium by diffusion and matrix erosion. Drug release was faster in pH 7.4 buffer than in distilled water: By the gradual pH change method, drug release was negligible in an acidic medium and gradually increased by the increasing pH. No statistically significant differences were observed between Eudragit and Aquacoat containing systems in the rat model for reducing carrageenin-induced paw edema. It was shown that the alginate-based beads with the added dispersions of water-insoluble polymers can sustain low molecular weight drugs more successfully. Working in an environment free of organic solvent is also art additional advantage.
Keywords: diclofenac sodium; alginate bends; aqueous polymer dispersions; aquacoat; eudragit; ALGINATE BEADS; RELEASE